REFLEKSI HISTORIS KEJAYAAN ISLAM DI MASA DINASTI ABBASIYAH - Akramun Nisa; St. Aisyah Abbas (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2022)
Abstract: The golden age of Islam that occurred in the time of the Abbasid dynasty is a historical fact. Compared to the progress obtained in the period the Prophet, Khilafoh Rasyidah,and Umayyads, Abbasids has more significant power. The achievement of Abbasid dynasty contributed the progress of political, military, economic, science and Islamic civilation. The rising of Abbasid Dynasty to power brought Islam to the new phase. In the Abbasids era the islamic politic dominated by Arabs has ended. the caliphs of Abbasid tried to establish a universal Islamic political entity based on the principle of equality between Muslim Arabs and non Arabs.